rosa.karschiewa@mail.ru FORMATION OF STUDENTS’ COMMUNICATIVE COMPETENCIES IN THE CREDIT-MODULE SYS: FORMATION OF STUDENTS’ COMMUNICATIVE COMPETENCIES IN THE CREDIT-MODULE SYS - Qarshiyeva, Ruzigul (Журнал иностранных языков и лингвистики, 2022)
This article discusses the formation of communicative competencies of students studying German as a second language in the credit module system and improving their knowledge of German.